Very slowly all at once - Schott, Lauren (Harper, 2026)
"A propulsive and wickedly entertaining debut thriller for fans of Laura Dave and Ashley Elston that explores the dark underside of the American dream, about a couple whose financial problems are seemingly answered when they begin receiving growing sums of money from an unknown source . . . a windfall that will carry an unthinkable price. Mack and Hailey Evans have worked hard to achieve their upper-middle-class life: promising careers, two beautiful children, and a brand-new house in the exclusive lakefront village of Bratenahl, Ohio. Not that everything's perfect--aging parents, problems at work, and even the upkeep on that gorgeous house have been causing these two increasing amounts of worry. When a small check appears in the mailbox from a mysterious company named Sunshine Enterprises, Mack assumes it's from his wealthy, estranged father, trying to buy his way back into their lives. Though he'd rather rip it up, Mack deposits the needed funds. To his surprise the checks keep coming--each for a larger amount larger than the last. When Hailey finds out what's going on, she has her own suspicions about the provenance of the payments. Despite growing uncertainty over the identity of their benefactor Mack and Hailey keep taking the money. After all, there are bills to pay. It is a choice with dark repercussions, as the couple soon learn the hard way that nothing in life is free. Suddenly, the Evans find themselves in a harrowing arrangement with someone who will stop at nothing to get a return on their investment"--Publisher's description.